Mario Blasco Lamenca (1931-2022) In memoriam - Burbano, Hernán (Revista de Ciencias Agrícolas, 2022)
With profound grief and high respect, an attempt to write a depiction of Dr. Mario Blasco Lamenca is presented here, a profile of a remarkable person who, during his life, stood out as a human being of high qualities and an insightful scholar and researcher with a reputation gained by his plentiful accomplishments. Mario Blasco Lamenca, who had understood the meaning of life the most and therefore assumed it with greatness, died in the early hours of January 3-4, 2022, in Zaragoza, Spain, surrounded by his family. In closing, it is necessary to affirm that writing about Dr. Blasco Lamenca means alluding to a genuinely illustrious man. His example, achievements, and attitude as a wise and good man make up a legacy that will last in the South of Colombia, in Pasto. He will remain highly appreciated, admired, and respected, especially in the Facultad de Ciencias Agrícolas of the Universidad de Nariño. Fortunately, the Revista de Ciencias Agrícolas will continue to bear witness to the ideals of its founder. Peace in the tomb of Professor Dr. Mario Blasco Lamenca.